Distribution of immunocompetent cells in the lungs of premature newborns on the background of some components of mother metabolic syndrome. - Rudyak, O. M. (Морфологія / Morphologia / Morfologìâ, 2011)
In immunohistochemical researching of the local immune system of the lungs (90 premature newborns, 29-33 weeks gestation), divided into 3 groups with respect to the components of mothers metabolic syndrome , the features and patterns of distribution, quantitative indicators of immune cells in the bronchial and respiratory departments are detected. It was determined that children who belong to group №1 (mothers hypertension and dyslipidemia ) have the total depression of T-lymphocytes (CD3), reduction of helper function (CD4), mixed reaction of suppressors (CD8), decreasing the number of B-lymphocytes - subpopulations (CD20), inhibition of macrophagic function (CD68). In group№2 (mothers diabetes type 2 and dyslipidemia) we observed depression of helper-suppressor functions (CD4, CD8), increasing of macrophagic reaction (CD68). Reducing of the absolute number of suppressor and cytotoxic T-lymphocytes subpopulations, a decreasing of B-lymphocytes (CD20) and inhibition of macrophagic functions (CD68) is observed in group№3 of children at the background of mothers adiposity and dyslipidemia. Reducing of expression of CD3 lymphocytes and levels of CD4 cells shows intensive reaction of cellular immunity in premature newborns. Comparative analysis of the immune status of the lungs of children in three groups with different components of mothers metabolic syndrome shows an acute disbalance of immunoregulation index, and the negative impact of mothers disease on histogenetic processes of respiratory organization.